Castor Oil Plant (Ricinus communis L.) Leaves Improve Dexamethasone-Induced Muscle Atrophy via Nrf2 Activation - Lee, Hyunjung; Kim, Young In; Kim, Min Jung; Hahm, Jeong-Hoon; Seo, Hyo Deok; Ha, Tae Youl; Jung, Chang Hwa; Ahn, Jiyun (Frontiers in Pharmacology, 2022)
Skeletal muscle atrophy is characterized by reduced muscle function and size. Oxidative stress contributes to muscle atrophy, but can be treated with antioxidants. This study investigated the antioxidant activity of a castor oil plant leaf (Ricinus communis L.) extract (RC) and its effects on muscle atrophy. Rutin was identified as the major compound among the thirty compounds identified in RC via LC-MS/MS and was found to inhibit dexamethasone (DEX)-induced muscle atrophy and mitochondrial oxidative stress. Rutin-rich RC showed DPPH and ABTS radical scavenging activities and efficiently reduced the DEX-induced myotube atrophy and mitochondrial oxidative damage in C2C12 cells. RC supplementation prevented the loss of muscle function and muscle mass in DEX-administered mice and ameliorated DEX-induced oxidative stress via Nrf2 signaling. Taken together, both RC and rutin ameliorated muscle atrophy and helped in maintaining redox homeostasis; hence, rutin-rich RC could be a promising functional food that is beneficial to muscle health.